Family Dispute Settlement In Islam: A Study of the Novel “Ipar Adalah Maut” - Anna Hadiyatullah Mahesy; Qurrotul Ainiyah (al-Afkar, Journal For Islamic Studies, 2025)
This article aims to provide an overview to all interested parties in solving problems in the family and analyze the resolution of family disputes from an Islamic perspective through the study of the novel "Ipar Adalah Maut". This research method uses a literature study (Library Research) with a Folklor approach and content analysis to identify the themes, and describe the phenomenon of disputes in the novel. The results of the study show: 1). The family conflict in this novel starts from the forbidden love committed by Aris and Rani even though Aris is still tied in marriage with Rani's older sister named Nisa. The conflict continued with adultery between aris and rani where the adultery was known by Nisa 2). Family conflict occurs because the character in this novel violates the boundaries of association with his brother-in-law who is not a muhrim. The resolution of conflicts that occur can be resolved in two ways, namely: religiously, the wife has the right to complain to the judge and the judge isallowed to separate due to harm. Meanwhile, the State Law of the wife can file a divorce lawsuit against the husband and sue criminally on charges of adultery.